Detailed morphological description of the mature larva of Anthrenus latefasciatus Reitter, 1892 (Dermestidae: Megatominae: Anthrenini) with comparisons to related species - Kadej, Marcin (Zootaxa, 2012)
A description of the last larval instar (based on exuvium) of Anthrenus latefasciatus Reitter, 1892 (Coleoptera:Dermestidae) is presented. New morphological characters of A. latefasciatus larvae such as general morphology ofantenna, epipharynx, mandibula, maxilla, ligula with labial palpi, hastisetae, legs, terga and condition of antecostal sutureare documented and discussed. General morphological differences among mature larvae of the following Anthrenusspecies are compared and summarized: A. coloratus Reitter, 1881, A. flavipes flavipes LeConte, 1854, A. fuscus Olivier,1789, A. latefasciatus Reitter, 1892, A. museorum (Linnaeus, 1761) A. oceanicus Fauvel, 1903, A. olgae Kalík, 1946, A.pimpinellae pimpinellae (Fabricius, 1775), A. sarnicus Mroczkowski, 1963, A. scrophulariae scrophulariae (Linnaeus, 1758), and A. verbasci (Linnaeus, 1767).